2016
DOI: 10.1080/10245332.2016.1148893
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease in Madhya Pradesh, Central India: A comparison of clinical profile of sickle cell homozygote vs. sickle-beta thalassaemia individuals

Abstract: The study revealed a high prevalence of SCD among scheduled caste, backward caste, and tribal communities. Dissemination of study findings, screening, pre-marriage counselling, and pre-natal diagnosis are fundamental to preventing or lowering of birth of sickle cell anaemia children in the affected populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
3
8
5
Order By: Relevance
“…Requirement for regular blood transfusions was higher among Hb SS (33.33%) than severe Hb S/b+ (2.70%) and Hb S/b 0 (14.30%) patients in the present study. These ndings differ from a study reported from Madhya Pradesh (India) in which 16.1% of Hb SS and 17.4% of SBT patients were on regular blood transfusion (31).…”
Section: Genetic Ndingscontrasting
confidence: 99%
See 2 more Smart Citations
“…Requirement for regular blood transfusions was higher among Hb SS (33.33%) than severe Hb S/b+ (2.70%) and Hb S/b 0 (14.30%) patients in the present study. These ndings differ from a study reported from Madhya Pradesh (India) in which 16.1% of Hb SS and 17.4% of SBT patients were on regular blood transfusion (31).…”
Section: Genetic Ndingscontrasting
confidence: 99%
“…In the present study, in patients who were not on transfusion, mean Hb F concentrations were 24.4%, 23.7% and 21.2% in Hb SS, severe Hb S/b+ and Hb S/b 0 patients, respectively. These values are in accordance with the observations from the Maharashtra (India) but are higher than the values observed in Madhya Pradesh (India) (31,34). The Hb F levels are much higher than those found in SCD patients of Sub-Saharan African origin, and levels greater than 20% would typically be associated with less severe clinical picture.…”
Section: Genetic Ndingssupporting
confidence: 90%
See 1 more Smart Citation
“…Requirement for regular blood transfusions was higher among Hb SS (33.33%) than SBT (5.88%) patients in the present study. These findings differ from a study reported from Madhya Pradesh (India) in which 16.1% of Hb SS and 17.4% of SBT patients were on regular blood transfusion [21]. Furthermore, twelve (23.53%) SBT patients had never received a transfusion in their lifetime.…”
Section: Discussioncontrasting
confidence: 89%
“…Another study done by Yadav et al, found higher incidence of splenomegaly in patients with Sickle cell anaemia and sickle β thalassemia. 10 In their study 68.8% children with homozygous SCA and 82.6% children with Sickle β thalassemia had splenomegaly. However, occurrence of recurrent bacteremia in spite of penicillin prophylaxis does indicate the non-functioning nature of spleen in central India population.…”
Section: Discussionmentioning
confidence: 99%